2016
DOI: 10.3389/fimmu.2016.00635
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt Blows: On the Functional Role of Wnt Signaling in Mycobacterium tuberculosis Infection and Beyond

Abstract: In recent years, it has become apparent that the Wnt signaling pathway, known for its essential functions in embryonic development and tissue homeostasis, exerts immunomodulatory functions during inflammation and infection. Most functional studies indicate that Wnt5a exerts pro-inflammatory functions on its cellular targets, which include various types of immune and non-immune cells. Wnt5a expression has also been linked to the pathogenesis of chronic inflammatory diseases. Activation of beta-catenin-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 139 publications
(164 reference statements)
2
24
0
1
Order By: Relevance
“…Increasing evidence suggests a regulatory function of Wnt proteins in inflammation, cancers, and infectious diseases. Other pathogens such www.nature.com/scientificreports www.nature.com/scientificreports/ as Mycobacterium tuberculosis, influenza, Hepatitis B virus, and certain bunyaviruses are known to manipulate the host Wnt network to enhance immune evasion and replication [68][69][70][71][72] . Specifically, we observed high expression of genes encoding the Wnt proteins, Wnt6 and Wnt5a, in fatal subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests a regulatory function of Wnt proteins in inflammation, cancers, and infectious diseases. Other pathogens such www.nature.com/scientificreports www.nature.com/scientificreports/ as Mycobacterium tuberculosis, influenza, Hepatitis B virus, and certain bunyaviruses are known to manipulate the host Wnt network to enhance immune evasion and replication [68][69][70][71][72] . Specifically, we observed high expression of genes encoding the Wnt proteins, Wnt6 and Wnt5a, in fatal subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Two main branches of classical WNT signaling cascades have been demonstrated: b-catenin-dependent (canonical) and b-catenin-independent (noncanonical) WNT signaling, the use of which depends on the context (19,20). Many studies indicated that WNT5A exerts proinflammatory functions on various types of immune and nonimmune cells, thus playing key roles in tissue homeostasis and modulation of immune responses in pathology (21,22). WNT5A not only contributes to maintain IFN levels in macrophages but also supports macrophage survival (20).…”
Section: Il-36g Promotes Killing Of Mycobacterium Tuberculosis By Macmentioning
confidence: 99%
“…Wnt5a wird bei Infektions-und Entzündungserkrankungen, wie Tuberkulose, Sepsis, Psoriasis, rheumatoider Arthritis und Atherosklerose, induziert [35]. Die β-Catenin-abhängige Wnt-Signalisierung verstärkt somit die Entzündungsreaktion [36].…”
Section: Stadien Der Hautregenerationunclassified